Role of dispute settlement in world trade law : some lessons from the Kodak-Fuji dispute - Linarelli, John (2000)
Sets forth the main findings of the Kodak-Fuji panel report. Examines the decision in the context of remedial activity that the United States attempted pursuant to its municipal law - the well-known section 301 of the Trade Act of 1974, as amended by the Omnibus Trade and Competitiveness Act of 1988. Provides an analytical framework for thinking about Kodak-Fuji, specifically, and about non-violation claims under Article XXIII : 1 (b), generally reaches the opposite conclusion of those reached by other scholars, who argue that Article XXIII should be interpreted narrowly.